Analysis of Plasmonic Waveguides and Gratings Using Implicit Finite-Difference Methods. (12th August 2010) - Shibayama, Jun; Yamauchi, Junji; Nakano, Hisamatsu
Abstract : Various metal-insulator-metal- (MIM-) type plasmonic waveguides and gratings are investigated numerically. Three gratings are treated: one is formed by alternately stacking two kinds of MIM waveguides, another by periodic changes in the dielectric insulator materials of an MIM waveguide, and the other by a periodic variation of the air core width in an MIM waveguide. The dispersion property of each MIM waveguide of which the grating consists is analyzed using the implicit Yee-mesh-based beam-propagation method. It is shown that the third one has a relatively large effective index modulation of the guided mode with a simple grating structure, while maintaining a low propagation loss. Further examination is given to modifications of this grating structure. The transmission characteristics are examined using the frequency-dependent implicit locally one-dimensional FDTD method. We discuss how the modified grating structure affects the bandgap of the transmission characteristics.